(untitled) (TAMADDUN NURI JURNALI, 2025)
This article deals with the ideological and artistic content of the novels in the “Harry Potter” series by British writer Joanna Kathleen Rowling, the place of the novel in world children’s literature, and its influence on Uzbek children’s literature. The article is also important in terms of introducing the writer’s creative laboratory.